2018
DOI: 10.1007/s00253-018-9501-8
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophic contribution to biodegradation of phenoxy acids in cultures enriched from a groundwater-fed rapid sand filter

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Enrichments amended with CH 4 were dominated by well-known methane oxidizers; these taxa were previously detected from CH 4 fed column reactors inoculated with sand-filter material (Papadopoulou et al, 2019). Dominant taxa in all enrichments yield over 50% of total community abundance, indicating that they outcompeted the other members, performing the anticipated function.…”
Section: Autotrophic Enrichmentsmentioning
confidence: 75%
“…Enrichments amended with CH 4 were dominated by well-known methane oxidizers; these taxa were previously detected from CH 4 fed column reactors inoculated with sand-filter material (Papadopoulou et al, 2019). Dominant taxa in all enrichments yield over 50% of total community abundance, indicating that they outcompeted the other members, performing the anticipated function.…”
Section: Autotrophic Enrichmentsmentioning
confidence: 75%
“…However, RSF performance for OMP removal is variable. Papadopoulou et al (2019) studied the biodegradation of 10 pesticides by MOB in column-scale RSF and found that removal efficiencies for diuron, isoproturon, linuron, 4-chloro-2-methylphenoxy acetic acid and MCPP were between 6.8% and 11.3%; the rest of the compounds (BAM, bromoxynil, cholrotoluron, and ioxynil) were not removed (Papadopoulou et al, 2019). The different elimination behaviors of OMPs in RSF were also verified by another microcosm experiment, where 42%-85% of MCPP, 15%-35% of bentazone, 7%-14% of glyphosate an 1%-3% p-nitrophenol were removed .…”
Section: Evaluation and Discussion On Omps Removal In Existing Rsf Symentioning
confidence: 99%
“…Although above studies show that biodegradation is the most important mechanism of OMPs removal (Table 1), only heterotrophic degraders of geosmin, MIB, BAM and MCPP have been defined in previous investigations (Albers et al, 2015;Elhadi et al, 2006;Feld et al, 2016) (Table 1). In addition, Hedegaard et al (2018) and Papadopoulou et al (2019) find that methanotrophic bacteria can remove OMPs from groundwater, while few investigations focus on the contribution of nitrifying bacteria to OMPs biodegradation in RSF for drinking water production. Thus, future research should include a broader set of OMPs and TPs, especially focusing on field-scale operations, as well as the detailed information of involved microbial populations in OMPs biodegradation in order to fully understand the potential of RSF to biodegrade OMPs.…”
Section: Evaluation and Discussion On Omps Removal In Existing Rsf Symentioning
confidence: 99%
See 2 more Smart Citations